Bad Faith as a Reason for Cancellation of Trademarks Registered More Than Five Years According to Law Number 20 of 2016 - Wijayanti, Henni; Salma, Dhiya (International Journal Labs, 2023)
According to Article 77 paragraph (2) of Law Number 20 of 2016 concerning Trademarks and Geographical Indications (UU MIG), a trademark cancellation lawsuit must be filed within five years from the date of trademark registration. Recently, a notable case involving the Cheong Kwan Jang trademark saw conflicting decisions from the Central Jakarta Commercial Court and the Supreme Court. Initially, the Central Jakarta Commercial Court rejected the application for cancellation of the Cheong Kwan Jang trademark filed by Korean Ginseng Corp. The court's reasoning was based on the inability of Korean Ginseng Corp. However, the Supreme Court, in its Decision Number 345 K/Pdt.Sus-HKI/2021, took a different stance and granted the request for cancellation of the mark that had been registered by PT. Mitra Sentosa International for more than five years. The basis for this decision was that the registration of the mark was deemed to have been done in bad faith, as outlined in Article 20 paragraph (3) of the MIG Law. Therefore, according to Article 77 paragraph (2) of the MIG Law, the brand could be canceled indefinitely, even though the five-year limit had passed. This study employs normative legal research, analyzing secondary data such as the Commercial Court Decision Number 15/Pdt.Sus/Merek/2020/PN.Niaga.Jkt.Pst and Supreme Court Decision Number 345 K/Pdt.Sus-HKI/2021, alongside relevant laws and regulations. The aim is to understand the reasons for the Commercial Court's rejection and whether the Supreme Court's decision aligns with the provisions of Article 77 of Law No. 20 of 2016.